2018
DOI: 10.1371/journal.pone.0207624
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of paddy rice leaf area index using machine learning methods based on hyperspectral data from multi-year experiments

Abstract: The performance of three machine learning methods (support vector regression, random forests and artificial neural network) for estimating the LAI of paddy rice was evaluated in this study. Traditional univariate regression models involving narrowband NDVI with optimized band combinations as well as linear multivariate calibration partial least squares regression models were also evaluated for comparison. A four year field-collected dataset was used to test the robustness of LAI estimation models against tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…These models also lack the ability to parameterize spatiotemporal variability [26]. PLSR has been considered to be a powerful alternative to univariate methods and provides better performance in most cases [27][28][29], although there is a study that reported the opposite results [22]. Moreover, the potential performance of the state-of-the-art machine learning methods, such as SVR, RF and ANN, has been explored in several studies [14,15,30].…”
Section: Introductionmentioning
confidence: 99%
“…These models also lack the ability to parameterize spatiotemporal variability [26]. PLSR has been considered to be a powerful alternative to univariate methods and provides better performance in most cases [27][28][29], although there is a study that reported the opposite results [22]. Moreover, the potential performance of the state-of-the-art machine learning methods, such as SVR, RF and ANN, has been explored in several studies [14,15,30].…”
Section: Introductionmentioning
confidence: 99%
“…Although simple to apply, the development of VIs are often time-, locationand scale-specific, (i.e., leaf or canopy-scale [18]). Furthermore, VIs make simplistic assumptions about the reflectance properties of a target and typically use only two to three fixed spectral bands [19], thus under-exploiting the potential of Earth observation multispectral sensors. Alternatively, machine learning approaches have the potential to generate adaptive, robust and non-linear relationships between all spectral bands and ground measurements [20].…”
mentioning
confidence: 99%
“…For example, spectral indexes, which have been widely used in the classification of middle-and low-resolution remote sensing imagery, are obtained by statistical analysis of the spectral information of the pixels [8]. Commonly used methods include various vegetation indexes [9,10], the Automated Water Extraction Index (AWEI) [11], the Normalized Difference Built-up Index (NDBI) [12], and the Remote Sensing Ecological Index (RSEI) [13]. The Enhanced Vegetation Index (EVI) [8], Normalized Different Vegetation Index (NDVI) [10], and other indexes derived from NDVI are effective at extracting vegetation information and have been widely used for extracting crop spatial distributions from low-resolution remote sensing imagery.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used methods include various vegetation indexes [9,10], the Automated Water Extraction Index (AWEI) [11], the Normalized Difference Built-up Index (NDBI) [12], and the Remote Sensing Ecological Index (RSEI) [13]. The Enhanced Vegetation Index (EVI) [8], Normalized Different Vegetation Index (NDVI) [10], and other indexes derived from NDVI are effective at extracting vegetation information and have been widely used for extracting crop spatial distributions from low-resolution remote sensing imagery. Some researchers have taken advantage of the high temporal resolution of middle-and low-spatial resolution remote sensing imagery to obtain the spectral index characteristics of a time series before extracting crop information with good results [14][15][16].…”
Section: Introductionmentioning
confidence: 99%